1999
DOI: 10.1046/j.1365-246x.1999.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

A Late Holocene geomagnetic secular variation record from Erhai Lake, southwest China

Abstract: A secular variation record of the geomagnetic field direction for the last 6.5 kyr has been obtained from the magnetization of sediment cores from Erhai Lake, southwest China. In order to make a comparison with this record, secular variation in eastcentral China was investigated by combining available magnetic field data from historical records and archaeomagnetic measurements since about 350 . The secular variation in Erhai Lake shows features consistent with the combined record, except for the oldest three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 9 publications
4
20
1
Order By: Relevance
“…It should be pointed out that the consistent age between cellulose-rich fraction and humic acid fraction extracted from plant fragment indicates no postburial effect and negligible vertical movement for humic acid fraction. It is also worth to note that our measured celluloserich fraction age (5050 ± 40 yr BP) is older than previous date, 4440 ± 130 yr BP, obtained in the same horizon by Hyodo et al (1999). The reason for the difference between the two measurements remains unclear.…”
Section: Radiocarbon Datescontrasting
confidence: 63%
See 3 more Smart Citations
“…It should be pointed out that the consistent age between cellulose-rich fraction and humic acid fraction extracted from plant fragment indicates no postburial effect and negligible vertical movement for humic acid fraction. It is also worth to note that our measured celluloserich fraction age (5050 ± 40 yr BP) is older than previous date, 4440 ± 130 yr BP, obtained in the same horizon by Hyodo et al (1999). The reason for the difference between the two measurements remains unclear.…”
Section: Radiocarbon Datescontrasting
confidence: 63%
“…3b. It can be found that there is a linear correlation between 14 C age and depth for the terrestrial macrofossils (plant fragment and shell) in ER3 and ER24 measured in this study and Hyodo et al (1999). Although there is a gap between 115 and 251 cm-deep, the best fitting gives the linear correlation (dashed line in Fig.…”
Section: Age and Depth Correlation Of Terrestrial Macrofossilssupporting
confidence: 51%
See 2 more Smart Citations
“…Around 7000 BC all data series consistently show a clear inclination minimum, which is predicted by pfm9k.1a and CALS10k.OL2c, but not by SHA.DIF.14k. This is because at that time the few available data (only 355 values for the whole interval of 12000 BC to 6000 BC) come from a small area at the western coast (Stockhausen 1998); WAI -Lake Waiau, Hawaii (Peng & King 1992); GNO -Lake Gnotuk, Australia (Barton & McElhinny 1981) and ERH -Erhai Lake, China (Hyodo et al 1999). (A colour version of this figure is available in the online version.)…”
Section: Discussionmentioning
confidence: 99%